2008
DOI: 10.1056/nejmoa0807773
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of RTS,S/AS02D Malaria Vaccine in Infants

Abstract: Please refer to usage guidelines at http://researchonline.lshtm.ac.uk/policies.html or alternatively contact researchonline@lshtm.ac.uk. Available under license: Copyright the publishersT h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 359;24 www.nejm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(149 citation statements)
references
References 10 publications
8
136
0
2
Order By: Relevance
“…3 Although the titer of anti-circumsporozoite antibodies is not an established correlate of the level of protection, an association with efficacy has been observed in several trials. [17][18][19][20][21] Infants may have mounted a lower immune response than older children owing to coadministration of RTS,S/AS01 with routine EPI vaccines, an inhibitory effect of maternally derived anti-circumsporozoite antibodies, an absence of priming with hepatitis B vaccine or with P. falciparum infection, or the infant's immature immune system.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the titer of anti-circumsporozoite antibodies is not an established correlate of the level of protection, an association with efficacy has been observed in several trials. [17][18][19][20][21] Infants may have mounted a lower immune response than older children owing to coadministration of RTS,S/AS01 with routine EPI vaccines, an inhibitory effect of maternally derived anti-circumsporozoite antibodies, an absence of priming with hepatitis B vaccine or with P. falciparum infection, or the infant's immature immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The RTS,S malaria vaccine candidate provides partial protection against clinical malaria in African children, which has been repeatedly demonstrated in Phase IIb and Phase III clinical trials (1)(2)(3)(4)(5). The RTS,S target is the Plasmodium falciparum circumsporozoite protein (CSP), and it has been shown to generate high antibody titers that remain above levels acquired naturally for years (6).…”
mentioning
confidence: 99%
“…The most advanced candidate malaria vaccine, RTS,S, is a pre-erythrocytic CSP-based sub-unit vaccine. Phase II trials of RTS,S/AS have demonstrated significant efficacy against time to first infection across all ages [4,37,38]. The principal component of RTS,S is the circumsporozoite antigen that induces high anti-CSP IgG antibody titres [10,36,39] and moderate CSP-specific T-cell responses [36,40,41] in vaccinated humans.…”
Section: Discussionmentioning
confidence: 99%